Integrated water resources management in the Mediterranean region dialogue towards new strategy - Ragab, Ragab; Rodriguez-Clemente, Rafael; Choukr-Allah, Redouane (Springer Netherlands, 2012)
This volume has 4 parts with 18 contributions and puts great emphasis on the importance of Integrated Water Resources Management IWRM as the way forward towards food, water, and energy security. It offers a ways and means to better manage the limited water resources; using the water more efficiently; adopting new policies in order to cope with climate change and the drought events; increasing water supply through the use of non conventional water resources, especially waste water; adopting stakeholders participation and information exchange and raising the of public awareness of the value of water.  An informative book for all those involved in all aspects of water resources containing valuable information to scientists, researchers, farmers, extension services, students and the public at large.